Basic Issues of Brandy Industry Waste Conservation - Sahakyan, Samvel; Yedoyan, Tatevik; Sukiasyan, Robert; Baghdagyulyan, Armine; Bakunts, Satenik (Geomatics and Environmental Engineering, 2023)
The purpose of the study is to cost-effective and environmentally friendly procedures for the condensation of waste generated from brandy production (distillery dreg) for agricultural use. The experiments were carried out between 2020–2022 under laboratory conditions. It has been shown that in order to reduce the significant cost of distillery dreg transportation, it is advisable to carry out its condensation by means of distillation. Laboratory studies and feasibility calculations revealed that distillery dreg may be condensed by up to five times, allowing for a corresponding reduction in transportation costs, while maintaining its quality indicators. It is suggested that the brandy alcohol distillation process be altered in a way that will allow for the production of condensed distillery dreg substance, with minimal additional energy expenditure and capital investment. The suggested method makes it possible to not only improve the ameliorative conditions of agricultural land, but also to address significant environmental protection issues.